Injuries in Athletics (Track and Field): A narrative review presenting the current problem of injuries - Edouard, P.; Dandrieux, P.-E.; Iatropoulos, S.; Blanco, D.; Junge, A.; Branco, P.; Chapon, J.; Mulenga, D.; Guex, K.; Guilhem, G.; Jacobsson, J.; Mann, R.; et al. (Deutsche Zeitschrift für Sportmedizin, 2024)
Objective: In Athletics (Track and Field), athletes can be affected by injuries, especially in their quest for top performance. Therefore, we aim to provide an overview of the current knowledge about the problem of injuries in Athletics. Main findings: It is necessary to maintain a clear definition of "injury" when stakeholders in Athletics discuss clinical, administrative, and/ or research perspectives. There are several possible methodological approaches to collect injury data in Athletics depending on the context, population, and injury definition. In general, about two thirds of Athletics athletes sustain at least one injury during an Athletics season, and there are about 100 injuries per 1000 registered athletes during an international championship. The injury rates and characteristics vary by sex and discipline. The injuries can affect athletes physically, psychologically, and socially, with short- and long-term consequences for musculoskeletal function, athletics performance and athletics career. Although it is logical to try to reduce the injury risk, little scientific evidence is currently available to help Athletics-related stakeholders. Conclusions: Injury can currently be considered as an omnipresent problem in Athletics, which affects their practice, with consequences on performance and health. Injury risk is today an undeniable part of the life of Athletics athletes, which implies that there is a pressing need to continue the development of injury risk reduction strategies, to scientifically evaluate their efficacy, and to implement them in sports practice.